Dekadensi Strategi Pembelajaran Tahfizh dan Tafsir Pondok Pesantren Tahfizh Al-Qur’an di Sulawesi Tenggara - Danial Danial; Nasri Akib (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2023)
This study aims to uncover and analyze learning methods, strategies and factors that support and hinder tahfizh and interpretation learning strategies at Pondok Tahfizh Baitul Qur'an al-Askar Kendari and Khalilul Qur'an Kolaka. This type of research is a descriptive qualitative research, using the theory of Umar's Al-Qur'an memorization strategy and the interpretation method of 'Abd Hay al-Farmawiy. The results of the study found that Pondok Tahfizh al-Askar Kendari and Pondok Tahfizh Khalilul Qur'an had carried out the steps of learning tahfizh in accordance with the formulation of behaviorism learning theory with the habit of memorizing which was repeated accompanied by a good stimulus and response from students, then using strategies that compiled by S. Nasution namely by identifying the specifications and qualifications of the students, then establishing a learning system, then determining the methods and techniques for learning tahfizh and interpretation, and evaluating learning. As for the tahfizh method based on the formulation of Umar's tahfizh method, there were differences in methods between the two huts, the tahfizh hut of Baitul Qur'an al-Askar uses three tahfizh methods, namely the Tariqah Wahidah, Muraja'ah and talqin teachings, while the Tahfizh Khalilul Qur'an hut Kolaka uses four methods, namely the Wahidah, Muraja'ah, Talqin, and sima'an methods. As for the interpretation of Pondok Tahfizh Baitul Qur'an al-Askar, it uses ijmaliy (global) interpretation and questions and answers in accordance with the division of interpretation according to 'Abd Hay al-farmawiy who is guided by an Ustadz, by explaining verse by verse according to systematics, then explanation of the general meaning, then a brief mufradat meaning, an analysis of the Arabic language rules and the general meaning of the verse. Whereas Pondok Tahfizh Khalilul Qur'an uses the question and answer method via online, and is not in accordance with the ijmaliy step. As for the supporting and inhibiting factors, there are two, namely internal and external, internal about the ability of students and murabbi/murabbiyah teachers, as well as existing facilities, while from external factors in the family environment, both mothers and colleagues. This finding has implications for contributing to the development of Al-Qur'am memorization and interpretation learning strategies, and can direct other researchers to conduct more comprehensive studies, especially regarding various problems of students in the process of learning tahfidh and interpretation as well as developing aspects of the Islamic boarding school model. Tahfizh both modern, classic, and medieval huts.